Effect of core/shell structured TiO2@C nanowire support on the Pt catalytic performance for methanol electrooxidation. Issue 11 (21st January 2016) - Sui, Xu-Lei; Wang, Zhen-Bo; Li, Cun-Zhi; Zhang, Jing-Jia; Zhao, Lei; Gu, Da-Ming
Abstract : Core/shell structured carbon-coated titania nanowires combine the advantages of structure and material, improving the electrocatalytic performance of Pt-based catalysts. Abstract : At present, low platinum catalysts have attracted much attention in the whole world. It is an effective strategy for reducing platinum loading to use an efficient support to enhance the catalytic activity. In this paper, a uniform structure of carbon and TiO2 nanowires is synthesized through a two-step hydrothermal reaction and used as an efficient Pt-based anode catalyst support. Physical characterization confirms the special core/shell structure. The carbonization temperature greatly affects the graphitization degree, porosity and surface chemical properties of the carbon shell. Electrochemical measurements indicate that the catalyst obtained at 800 °C has excellent electrochemical activity and durability. Its electrochemically active specific surface area is much higher than that of Pt/C. Its activity for methanol oxidation is about 1.4 times higher than that of Pt/C. The enhanced performance is attributed to the design of the special core/shell structure. The uniform dispersion of carbon and titania nanowires produces a strong synergistic effect and generates highly active Pt loading sites. The carbon shells can greatly improve the electronic conductivity and suppress the crystal growth of TiO2 during calcination. Meanwhile, a large number of defects within the carbon shells are also conducive to the dispersion of Pt nanoparticles. In addition, the core of TiO2 nanowires can enhance the hydrophilicity of the carbon shell and produce a strong metal–support interaction with Pt nanoparticles, which improve the activity and durability of catalysts.